Building Through Crisis: Conceptual Metaphor and Developmentalist Framing in Jokowi's Pandemic Economic Discourse (2020–2022) - Dita Aulia; Jismulatif Jismulatif; Dahnilsyah Dahnilsyah (Lembaga Teewan Journal Solutions, 2026)
This study examines conceptual metaphor use in President Joko Widodo's (Jokowi's) pandemic economic speeches from 2020 to 2022, a period spanning the acute COVID-19 crisis through Indonesia's post-pandemic recovery. Drawing on Conceptual Metaphor Theory (CMT) and the Metaphor Identification Procedure (MIP), with corpus-assisted analysis using AntConc, this study analyzes seven official speeches to identify dominant metaphorical frames and their rhetorical functions. The findings reveal that Jokowi's pandemic economic discourse is predominantly structured around a developmentalist metaphor system, with the Development Frame (14 instances) and Economy Frame (13 instances) together accounting for the majority of the 38 metaphorical expressions identified. Rather than foregrounding crisis as threat or danger, Jokowi consistently reframes the pandemic as a platform for economic transformation and forward movement. Key conceptual metaphors include development is a journey, economy is a living organism, and economy is a machine, all of which project active government agency and optimistic national trajectory. Crisis metaphors appear minimally and are quickly redirected toward development and recovery framing. This pattern is interpreted in relation to Jokowi's populist-developmentalist leadership ideology, which constructs political legitimacy through tangible outcomes and collective resilience rather than institutional reform or crisis dramatization. The findings contribute to the growing body of literature on political metaphor in non-Western contexts and offer implications for understanding how crisis communication strategies are shaped by ideological orientation and leadership identity.